Early outcomes of peroral endoscopic myotomy with fundoplication for achalasia cardia – Is it here to stay?. Issue 4 (28th August 2020) - Patil, Gaurav; Dalal, Ankit; Maydeo, Amit
Abstract : Background: Peroral endoscopic myotomy with fundoplication (POEM‐F) has garnered widespread attention since it tries to achieve an appropriate antireflux procedure during the same setting. The outcomes of POEM‐F are currently unexplored. Methods: Patients who underwent POEM‐F at our center were retrospectively studied to assess its safety and early outcomes. Results: Twenty patients [70% male; median age 32 years (range 25–41)], with a median symptom duration of 2.1 years (range 1.5–3.7) with achalasia were included. POEM‐F procedure was completed in a median of 118 min (range 90–160), with 17/20 (85%) technical success. The median hospitalization was 4 days (range 2–7). Capnothorax ( n  = 3), resolved spontaneously ( n  = 2) in 4–6 h, while in one patient ( n  = 1) the endoscope inadvertently entered into the thoracic cavity for which prophylactic intercostal drain was required. Capnoperitoneum was seen in 17/17 (100%) patients who underwent fundoplication, subcutaneous emphysema in 8/17 (47%) patients. At 1‐month follow‐up endoscopy, 5/17 (29.4%) patients had loosening of the fundal wrap, 3/17 (17.6%) patients had ulceration in fundus and in gastroesophageal junction due to underlying hemoclips. At 3 months, loosening of the fundal wrap was seen in 7/17 (41.2%) patients. A 24‐h pH‐metry revealed abnormal esophageal acid exposure in 7/17 (41.2%) patients, while it was normal in those patients in whom the fundal wrap was maintained. 10/17 (58.8%) patients were off proton pump inhibitors. Conclusion: POEM‐F is technically feasible with reasonable short term success. However, the durability, early success and safety of POEM‐F need reassessment in long‐term studies before being applied in clinical practice.